(3GdJjSjQ aj GdeOGhI hGdJOHjQs - (3YHO Gdedc Hf RgQ Hf YHO Gdedc, CHh eQhGf,J (B557 (3g` s
(3ChdgG (B:s
(3Efi hGdTGgO Gddg de CVY gPG GdcJGH EdG hbO dRfi GdEVWQGQ dTOI GdYRe , hHGdCeQ Gdbhi GdLRe Edi hVYg s
(3BNQgG (B:s
(3hEPG bO CJjJ ef Gdbhd eG CQOJ EjJGAg , aCfG bGWY Gdbhd EPG bO ESJeeJg , hHGddg GdJhajb dGQH ZjQg Je cJGH GdJjSjQ aj GdeOGhI hGdJOHjQ s
(3Vef eLehY s
(3GfXQ eY GdCZPjI (B- (3fSNI HGQjS Qbe (B"330"s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B303s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B71 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs